An asymptomatic tongue nodule - Richa; Jay Gopal Ray; Sweta Pattanayak; Vibha (Wolters Kluwer Medknow Publications, 2012)
Cysticercosis is a major health concern in developing countries, as it is a major cause of seizures in these countries. The tissues commonly affected are the neural tissues, muscle, heart, lungs, liver, subcutaeneous layers and peritoneum, but oral manifestations are rare. Present case is of an asymptomatic tongue nodule which was diagnosed as cysticercosis on histologic examination. Thus, emphasizing the importance of routine microscopic examination and diagnosis of apparently innocuous lesions of the oral cavity.